2022
DOI: 10.33650/al-tanzim.v6i1.3228
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Culture, Principal Leadership and Motivation on Teacher Performance in Madrasah

Abstract: This study aims to determine whether direct and indirect effects of organizational culture, principal leadership, and motivation on teacher performance at Madrasah Aliyah Irsyadul Islamiyah. The type of research used is a quantitative research using multiple linear regression formulas and flow analysis as its development. This study found that: 1) there was a significant influence between teacher motivation and teacher performance of 0.570. The contribution given by teacher motivation to teacher performance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
3
23
0
5
Order By: Relevance
“…The success or failure of an organization depends on the activities and creativity of employees (Gultom & Situmorang, 2020). Motivation will also encourage someone to work better to achieve the expected performance to get what they need (Hasibuan, 2022). Therefore, motivation is essential for leaders and employees to increase morale and performance (Haryono et al, 2020).…”
Section: Resultsiand Discussionmentioning
confidence: 99%
“…The success or failure of an organization depends on the activities and creativity of employees (Gultom & Situmorang, 2020). Motivation will also encourage someone to work better to achieve the expected performance to get what they need (Hasibuan, 2022). Therefore, motivation is essential for leaders and employees to increase morale and performance (Haryono et al, 2020).…”
Section: Resultsiand Discussionmentioning
confidence: 99%
“…A job always has work steps (procedures); work procedures always increase work results by work demands. If the procedure carries out a job, it will arrive at the desired work result (Hasibuan, 2022).…”
Section: There Is a Direct Influence Of Competence (X1) And The Use O...mentioning
confidence: 99%
“…The performance benchmark is job demands that describe the work to be achieved. How far a person can do the job compared with the results achieved is called a person's performance (Hasibuan, 2022). Therefore, good competence so that teachers can more easily convey the subject matter to learners requires skills and understanding and use of information technology.…”
Section: There Is a Direct Influence Of Competence (X1) And The Use O...mentioning
confidence: 99%
“…The results of Hasibuan's research also found t a significant influence between teacher motivations and teacher performance. Teacher motivation significantly improves teacher performance (Hasibuan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%